Performance-related Pay and the UK Gender Pay Gap - Melanie Jones; Ezgi Kaya (Global Labor Organization (GLO), 2022)
This paper explores the role of performance-related pay to the UK gender pay gap at the mean and across the earnings distribution. Applying decomposition methods to data from the Annual Survey of Hours and Earnings, we find that performance-related pay is an important but neglected factor, with the lower probability of females being employed in performance-related pay jobs explaining 12 per cent of the observed mean gender pay gap and making a larger contribution than many work-related characteristics routinely included in studies of this nature. Driven by its influence in the private sector, employment in performance-related pay jobs is more important in explaining the gender pay gap at the top end of the wage distribution, consistent with gender differences in receipt of bonus payments. Gender differences in the reward to performance-related pay jobs have a further, but more modest, role in widening the national and private sector mean gender pay gap.
Keywords: J31; J33; J45; J71; 330; gender pay gap; performance-related pay; earnings distribution; sector